TABLE OF CONTENTS (Theoretical and Applied Linguistics@ro, 2025)
The Multiple Faces of Linguistic ResearchI. Formal and Functional Approaches to SyntaxII. Discourse and SocietyIII. Mapping the Lexicon: Methodological PerspectivesIV. Discursive Practices in Educational SettingsV. Books, Voices, Perspectives